2012
DOI: 10.1016/j.cognition.2012.05.018
|View full text |Cite
|
Sign up to set email alerts
|

First impressions: Gait cues drive reliable trait judgements

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Cognition. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. A de nitive version was subsequently published in Cognition, 124(3), September 2012, 10.1016/j.cognition.2012.05.018Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 50 publications
(88 reference statements)
5
49
0
Order By: Relevance
“…The current research failed to find relationships between men's self-reported personality and women's ratings of men's personality from men's dance movements. Thus, women were not able to accurately assess men's personality from dance movements-a result that corroborates research investigating relationships of self-reported personality with observer reports of personality based on gait (Thoresen et al 2012). Although research on personality perception from faces suggests there is a "kernel of truth" in trait impression (e.g., Berry 1990;Penton-Voak et al 2006), accurate trait ratings may not be derivable from body movement.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The current research failed to find relationships between men's self-reported personality and women's ratings of men's personality from men's dance movements. Thus, women were not able to accurately assess men's personality from dance movements-a result that corroborates research investigating relationships of self-reported personality with observer reports of personality based on gait (Thoresen et al 2012). Although research on personality perception from faces suggests there is a "kernel of truth" in trait impression (e.g., Berry 1990;Penton-Voak et al 2006), accurate trait ratings may not be derivable from body movement.…”
Section: Discussionsupporting
confidence: 48%
“…For example, Thoresen et al (2012) presented point-light walking of motion-captured men and women to participants who were asked to rate them on major personality dimensions. As in previous studies (e.g., Ambady and Rosenthal 1993;Montepare and Zebrowitz-McArthur 1988), there was high agreement among raters, although there was no correlation of self-reported with perceived personality.…”
Section: Introductionmentioning
confidence: 99%
“…Weege et al (in press a) showed that men’s self-reported (NEO-FFI) personality scores did not correlate with women’s ratings of men’s personality standings, i.e., women were not able to accurately assess men’s personality from dance movements—a result that corroborates research investigating relationships of self-reported personality with observer-reports of personality based on gait (Thoresen et al, 2012). However, women’s ratings of a man’s dance attractiveness correlated negatively with their ratings of his neuroticism, and positively with their ratings of his conscientiousness.…”
Section: Cross-cultural Perception Of Body Movementmentioning
confidence: 54%
“…Although the time required to accurately assess another person based on movement cues is not yet known, one can speculate that it is longer than that reported for face perception. Thoresen et al (2012) presented point-light walkers to participants and identified the movement components that accounted for personality judgments. Observers made reliable trait judgments using a small number of movement components.…”
Section: Perception Of Body Movementmentioning
confidence: 99%
“…Each video was rated on all 6 Effort Shape scales (5-point Likert scales from [Thoresen et al 2012] presented in Figure 1), resulting in 312 ratings in total. The experiment was then divided into 24 counterbalanced blocks: 2 Character-type (Hero, Villain) × 2 Gender (Female, male) × 6 Effort Shape scales.…”
Section: Methodsmentioning
confidence: 99%